Integrasi IoT dalam Sistem Monitoring dan Kontrol Suhu Inkubator Mikroba Skala Laboratorium - Nurluthfiyadi Ni'maturrakhmat, Viko; Suryadharma, Bertung (Jurnal Pengelolaan Laboratorium, 2025)
Agro-Industry Management and Technology Laboratory is a laboratory unit used for educational activities, namely practicums and research. In these activities, an incubator is needed to grow microorganisms. Internet of Things (IoT) is a concept where objects can transfer and receive data through a network without requiring human-to-human or human-to-computer interaction. The development of technology allows for monitoring and remote control processes via smartphones. This study aims to design a smart microbial incubator with the same working principle as a conventional incubator. It has the advantages in terms of practicality and system integration of tools, low production costs, and can control and monitor the incubator temperature in real time. This study uses a design and construction method so that systematic steps are needed to produce appropriate products, starting from identifying the need for tools and materials, system design, software development, testing and evaluation. The results of the incubator temperature test, as determined by comparing the readings of the IR thermometer, are known to have a low average error rate of 0.47 °C. This study can design an incubator with a temperature controller and monitoring via a smartphone using the Blynk application.